In vitro Assays and Imaging Methods for Drug Discovery for Cardiac Fibrosis - Palano, Giorgia; Foinquinos, Ariana; Müllers, Erik (Frontiers in Physiology, 2021)
As a result of stress or aging, cardiac fibrosis is characterized by an excessive deposition of extracellular matrix components resulting in pathological remodeling, tissue stiffening, ventricular dilatation and cardiac dysfunction which contribute to heart failure and eventually death. Currently, there are no effective therapies specifically targeting cardiac fibrosis, partially due to limited understanding of the pathological mechanisms and the lack of predictive in vitro models for high-throughput screening of anti-fibrotic compounds. The use of more relevant cell models, three dimensional (3D) models and co-culture systems, together with high-content imaging and machine learning-based image analysis, is expected to improve predictivity and throughput of in vitro models for cardiac fibrosis. In this review, we present an overview of available in vitro assays for cardiac fibrosis. We highlight the potential of more physiological 3D cardiac organoids and co-culture systems and discuss high-content imaging and automated Artificial Intelligence (AI)-based image analysis as key methods able to capture the complexity of cardiac fibrosis in vitro. As 3D and co-culture models will soon be sufficiently mature for application in large-scale preclinical drug discovery, we expect the combination of more relevant models and high-content analysis to greatly increase translation from in vitro to in vivo models and facilitate the discovery of novel targets and drugs against cardiac fibrosis.